Preliminary evaluation of elite clones of cardamom (Elettaria cardamomum Maton) for yield and yield parameters in clonal nursery - HOSMANI, V S KORIKANTHIMATH, RAVINDRA MULGE, M M (Journal of Spices and Aromatic Crops, 1997)
Twelve elite clones of cardamom (Elettaria cardamomum) were assessed for yield and yield parameters at Appangala (Karnataka, India) in the clonal nursery in two batches of planting. Among them, Sel. 9, Sel. 7 and Sel. 4 were significantly superior for yield and yield parameters, with higher number of panicles and capsules per plant, wet weight of capsules per plant and dry capsule yield per hectare. Early planting of clones was ideal for better establishment, suckering and yield under irrigated conditions.